Pretreatment with dual antiplatelet therapy in patients with ST-elevation myocardial infarction. - Yudi, M.; Farouque, O.; Andrianopoulos, N.; Ajani, A.; Brennan, A.; Lefkovits, J.; Reid, Christopher; Chan, W.; Duffy, S.; Clark, D.; Melbourne Interventional Group. (2017)
BACKGROUND: The optimal time to administer P2Y12 inhibitors in patients with ST-elevation myocardial infarction (STEMI) remains to be defined. We sought to assess whether a pretreatment strategy was associated with improved coronary reperfusion and clinical outcomes. METHODS: Consecutive patients from the Melbourne Interventional Group registry (2005-2014) who presented with STEMI and underwent primary PCI were included. Those who received any P2Y12 inhibitor prior to arrival in the cardiac catheterisation laboratory were included in the pretreatment group. The primary endpoints were the proportion of patients with initial TIMI flow grade <3 and in-hospital bleeding. The secondary endpoints were 12-month mortality and major adverse cardiovascular events (MACE). RESULTS: Of the 2,807 patients included, 892(31.8%) received pretreatment. Clopidogrel was the most common P2Y12 inhibitor used (79.6%). Pretreatment was associated with less thromboaspiration and GPIIb/IIIa inhibitor use (both P?<?0.01). Pretreatment was not associated with lower rates of TIMI flow <3 on initial angiogram (78.0% vs. 80.7%, P?=?0.18) nor with increased in-hospital bleeding (3.6% vs. 3.9%, P?=?0.67). Pretreatment was associated with lower 12-month mortality (4.7% vs. 7.0%, P?=?0.02) but similar MACE rate (13.0% vs. 14.1%, P?=?0.43). Multivariate analysis revealed pretreatment was not an independent predictor of 12-month mortality (OR 0.79; 95% CI 0.5-1.3, P?=?0.32). CONCLUSION: Pretreatment with a P2Y12 inhibitor in patients with STEMI was not routine practice in our Australian cohort and was not associated with improved coronary reperfusion or clinical outcomes. Larger studies are required to definitively ascertain the risk/benefit ratio of dual antiplatelet therapy pretreatment in STEMI.